Study Of Islamic Education Adaptation Of The Radio Raka Swara Da'wah Broadcast Program In Maintaining Its Existence In The Digital Age: ADAPTASI PROGRAM SIARAN DAKWAH RADIO RAKA SWARA DALAM MEMPERTAHANKAN EKSISTENSINYA DI ERA DIGITAL - Yaspida, Ruslan Hamid (TA`DIBUNA, 2025)
The development of the digital era has brought major changes in the way people access and consume media, which has had a significant impact on the sustainability of conventional media, including radio. Radio Raka Swara, as a local broadcasting station focusing on Islamic preaching content, has attempted to adapt to these dynamics in order to maintain its existence amid increasingly fierce competition from digital media. From the perspective of Islamic education studies, religious radio plays an important role as a means of non-formal education that can expand public access to Islamic knowledge and values. The purpose of this study is to identify and analyze the adaptation strategies employed by Radio Raka Swara in maintaining the sustainability of its religious programs while building audience trust. The research method used a descriptive qualitative approach through in-depth interviews, direct observation, and documentation study. The results show that Radio Raka Swara has successfully utilized various digital platforms such as YouTube, Instagram, TikTok, Spotify, and its own mobile application. The use of these platforms allows broadcasts to reach a wider audience, including international listeners, and to present da'wah content that is more visually appealing and interactive. Other strategies implemented include the use of traffic data for program evaluation, two-way interaction through live streaming features, and content adaptation to cross-generational characteristics. The implementation of these strategies is evident in the development of social media integration with radio broadcasts, training broadcasters to master digital broadcasting, and collaboration with online da'wah communities. Despite facing limitations in resources and promotional funds, Radio Raka Swara has proven that radio remains relevant if it transforms in line with technological developments and audience needs. Further research is recommended to examine the long-term impact of digitization on the da'wah consumption patterns of the younger generation, as well as to explore in greater depth sustainable business models that can truly support the financial independence of da'wah-based radio media in the modern digital era